Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13018-020-02089-4
|View full text |Cite
|
Sign up to set email alerts
|

Age over 65 years and high levels of C-reactive protein are associated with the risk of preoperative deep vein thrombosis following closed distal femur fractures: a prospective cohort study

Abstract: Background In this study, we investigated the epidemiological characteristics and predictors of preoperative new-onset deep vein thrombosis (DVT) in adult patients with closed distal femur fractures (DFFs). Methods The study was designed as a prospective cohort trial at the Third Hospital of Hebei Medical University. From October 2018 to June 2020, a total of 160 patients with closed DFFs were enrolled to assess the location and prognosis of preoperative DVT. The patients were followed up for 2 months. Duplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 31 publications
(39 reference statements)
2
28
0
Order By: Relevance
“…Niu [ 25 ] found that the risk was 2.02 times greater in elderly patients with hip fracture with a preoperative PLT count> 220 × 10 9 /L compared to patients without DVT. Another study [ 26 ] also found that elderly patients with femoral fractures had a 2.55-fold risk of developing DVT before operation when PLT count> 217 × 10 9 /L. In this study, multiple logistic regression analysis showed that PLT count was one of the independent risk factors for DVT ( P < 0.05), with an AUC = 0.642 (95% CI: 0.569 ~ 0.714), cutoff value of 200.5 × 10 9 /L, OR = 1.008 (95% CI: 1.002 ~ 1.015), and sensitivity and specificity of 38.9 and 85.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Niu [ 25 ] found that the risk was 2.02 times greater in elderly patients with hip fracture with a preoperative PLT count> 220 × 10 9 /L compared to patients without DVT. Another study [ 26 ] also found that elderly patients with femoral fractures had a 2.55-fold risk of developing DVT before operation when PLT count> 217 × 10 9 /L. In this study, multiple logistic regression analysis showed that PLT count was one of the independent risk factors for DVT ( P < 0.05), with an AUC = 0.642 (95% CI: 0.569 ~ 0.714), cutoff value of 200.5 × 10 9 /L, OR = 1.008 (95% CI: 1.002 ~ 1.015), and sensitivity and specificity of 38.9 and 85.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another study stated that the sensitivity and specificity of the D-dimer level suggesting DVT were 71.4 and 78.6%, respectively, when the D-dimer level was>2.79 mg/L. [ 22 ] The optimal critical value of D-dimer was 1.0 mg/L, approximately twice the upper limit of the standard (0.5 mg/L) in patients with femoral fractures over 65 years old in a recent prospective study [ 26 ], and the risk of preoperative DVT increased by 3.5 when the D-dimer level was >1.0 mg/L. Therefore, appropriate adjustment of the cutoff value is necessary and valuable for the clinical judgment of perioperative complications of DVT in patients of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [ 25 ] reported that an advanced age above 60 years was a significant predictor of DVT in patients with fractures below the hip. In a prospective cohort study, Zhang et al [ 26 ] reported that age over 65 years was associated with the formation of preoperative DVT in distal femur fractures. Goel et al [ 27 ] found age > 40 years was an independent predictor for DVT following fractures below the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, Zhang et al . prospectively studied 160 patients over 65 years of age with distal femoral fractures and found that the incidence of preoperative DVT detected by DUS was 52.5% (84/160) [ 18 ]. The results of the current study showed a low incidence of preoperative DVT (26.4%, 114/432).…”
Section: Discussionmentioning
confidence: 99%
“…Age is an important factor in the formation of DVT, especially in patients with trauma [ 10 , 18 , 20 ]. Among the 432 patients (aged 18–90 years) with femoral shaft fractures in the present study, it was evident that each additional 10 years of age was associated with a 20% increase in risk of preoperative DVT (P < 0.002).…”
Section: Discussionmentioning
confidence: 99%